2011
DOI: 10.5123/s1679-49742011000200003
|View full text |Cite
|
Sign up to set email alerts
|

Homicídios e condição de vida: a situação na cidade do Recife, Pernambuco

Abstract: ResumoObjetivo: o estudo analisou os diferenciais da mortalidade por homicídios entre residentes segundo estrato de condição de vida e bairro, no Recife, no período [2004][2005][2006]. Metodologia: estudo ecológico exploratório de múltiplos grupos de base censitária; foi calculado o coeficiente acumulado de mortalidade por homicídios para o conjunto do Município e para estratos -regiões-bairros classificados por condição de vida. Resultados: a análise mostrou um coeficiente acumulado para o Recife de 203,3/100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
2
5
0
Order By: Relevance
“…In terms of the analysis of the conditions of victimization, the authors of the present study agree with the findings of Adorno [ 41 ] and Barbosa et al [ 32 ]. These authors considered that areas with socioeconomic inequality, allied to segregation and social exclusion, exhibit higher numbers of violent cases due to the deterioration of physical and social infrastructure.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In terms of the analysis of the conditions of victimization, the authors of the present study agree with the findings of Adorno [ 41 ] and Barbosa et al [ 32 ]. These authors considered that areas with socioeconomic inequality, allied to segregation and social exclusion, exhibit higher numbers of violent cases due to the deterioration of physical and social infrastructure.…”
Section: Discussionsupporting
confidence: 93%
“…The variables that most often contributed to the explanation of this phenomenon were identified. As the aim of the present study was to analyze the existence of socio-spatial vulnerability, variables that evidenced poorer socioeconomic indicators, residential infrastructure and neighborhood infrastructure of the residences of victims were highlighted [ 8 , 17 , 28 – 32 ]. The following were analyzed: percentage of homes with eight residents; percentage of homes with no monthly income; percentage of heads of households with no monthly income; percentage of homes with no exclusive bathroom or with no bathroom; percentage of homes with electricity of an unknown origin and unofficial connection; percentage of homes with no connection to the water supply or sewage supply and no trash pickup; percentage of homes with no streetlights in the neighborhood; and percentage of homes with open-air sewage in the neighborhood.…”
Section: Methodsmentioning
confidence: 99%
“…As observed, the dissemination of the infection among the pregnant women was not random, as it showed a cluster pattern according to the Moran Index, indicating that neighboring regions show similarities. Clusters were evidenced in the neighborhoods Recife, São José and Guabiraba, considered socially underprivileged in studies that support distinctions in these regions, measured by the indicator Living conditions, revealing them as areas with precarious living conditions, in terms of social, economic and infrastructural aspects 15 - 16 .…”
Section: Discussionmentioning
confidence: 99%
“…The neighborhoods Recife and São José, identified as high-risk areas for the vertical transmission of HIV, are neighbors and located in the central and most urban part of the city. The neighborhood Recife is a touristic harbor area and trading post 15 .…”
Section: Discussionmentioning
confidence: 99%
“…The high coefficient of intentional homicide in the Calçada neighborhood, which was six times higher than that of Salvador, may be related to a proportion of over 80% of black males aged 15 -49 and worse sociodemographic conditions in this neighborhood. In a similar study, Barbosa et al 23 observed higher coefficients of homicide in neighborhoods with the worst indicators in the city of Recife from 2004 -2006. A problem that has been highlighted in the literature regarding the variability of the rates of an event due to a low number of cases could also have affected this finding 17 .…”
Section: Discussionmentioning
confidence: 76%